From Tradition to Simulation: Representation of Asian Culture in The Sims 4: For Rent - Aulia Rahmawati; Mila Aminah Ramadhani (Lavish Opulent Education, 2025)
This Journal aims to examine how Asian culture is represented in the video game The Sims 4: For Rent. As one of the most influential forms of interactive media, video games have the potential to convey cultural narratives through visuals, characters, and gameplay mechanics. This research adopts a qualitative approach using visual analysis based on Stuart Hall’s theory of representation and Gillian Rose’s visual methodology, particularly the site of the image (itself) and Discourse Analysis II. Data were collected through visual observation of elements reflecting Asian culture in the game, including architecture, clothing, objects, and social activities. The findings reveal that Asian culture, especially Southeast Asian culture, is represented through visual symbols such as traditional boarding house architecture, batik clothing, local cuisine, and communal values like mutual cooperation. These representations are framed positively, portraying warmth and the richness of local traditions. This study concludes that The Sims 4: For Rent functions not only as a form of entertainment but also as a cultural learning medium that shapes global perceptions of Asian identity.